Teacher-parent collaboration in individualized education program (iep) for special education - Mislan, Nora; Kosnin, Azlina; Yeo, Kee Jiar (2008)
The aim of this study is to develop a collaboration model between teachers and parents in special education school in Johor Bahru, Malaysia. Teachers and parents are expected to work in partnership and collaborate to determine the goals and objectives that are appropriate to the students’ development in various aspects. It is recognized that educational needs are difficult to be fulfilled unless individualized attention is given to these students. Thus, the IEP process should be taken seriously as it is one of the most crucial factors in the bid to improve on the services provided for students with disabilities. Writing and executing an effective IEP is critical since IEP provides the basis for quality education for these children. The sample in this study involved the parents whose children were being recognized as needing Individualized Education Program (IEP) and the teachers who were engaged in the implementation of the IEP process. Taking this matter into consideration, feedbacks from parents regarding their personal views as well as teachers’ objectives and visions would be invaluable in developing effective special education programs.